PACKAGING WASTE MANAGEMENT ON EXAMPLE OF CITY ZIELONA GÓRA - Joanna ZARĘBSKA (Management Systems in Production Engineering, 2012)
The article presents the legal requirements of the European Union's packaging waste, and their most recent transposition into Polish law. The author has attempted to describe selected achievements of the Department of Public Utilities and Housing (DPUaH) in Zielona Góra, which for many years on behalf of the city, in a systematic way it’s developing municipal waste management system (including packaging), consistent with EU policies and objectives of sustainable development. The deficiencies and weaknesses in the system are taken into consideration, whose liquidation is a priority for future investment of DPUaH consistent with the Waste Management Plan for the City of Zielona Góra.